USER INTERFACE ANALYSIS OF THE DAMRI APPS APPLICATION USING THE HEURISTIC EVALUATION METHOD - Siwi, Sinta Raka; Adriyanto, Andreas Rio (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
This study evaluates the user interface (UI) of the DAMRI Apps applica- tion using the heuristic evaluation method to assess user satisfaction and identify usability issues. Despite its growing popularity, with 209,832 new users from 2022 to 2023, and a high user rating of 4.3, users have reported various problems affecting comfort and safety. Three UI/UX ex- perts conducted the evaluation based on Nielsen's ten usability principles, assessing the application's interface and categorizing issues by severity. The evaluation process involved observing a video demonstration of the ticket booking process and hands-on testing of the app. Results revealed that while most issues were minor (average severity level 2), significant problems (level 3) were identified in three key areas: visibility of system status, user control and freedom, and error prevention. Major issues in- cluded lack of clear information on ticket schedules, confusing interface elements, and poor color choices leading to user errors. The study con- cludes that the DAMRI Apps interface requires substantial improvements in specific areas to enhance user experience. Recommendations include providing clearer information, implementing wizard steps and timers, separating menu selection and form filling pages, and optimizing color schemes for better usability.